Development of Vegetal Based Thermal Plasters with Low Environmental Impact: Optimization Process through an Integrated Approach. (November 2015) - Carbonaro, Corrado; Tedesco, Silvia; Thiebat, Francesca; Fantucci, Stefano; Serra, Valentina; Dutto, Marco
Abstract: The use of thermal insulating plasters represents an effective solution in energy retrofit of existing buildings. Thermal properties are usually improved through the addition on the plaster formulation of Light Weight Aggregates, as expanded polystyrene and perlite. The drawback of these thermal plasters is the higher environmental impact, especially when added to natural binders, as natural hydraulic lime. Within a research activity a process of optimization was followed in order to get the most effective blend, applying iteratively the LCA methodology, measuring the thermal conductivity and testing the environmental impact in terms of Volatile Organic Compounds and formaldehyde emission rates.